Downregulation of Neurofilament Light Chain Expression in Human Neuronal-Glial Cell Co-Cultures by a Microbiome-Derived Lipopolysaccharide-Induced miRNA-30b-5p - Pogue, Aileen I.; Jaber, Vivian R.; Sharfman, Nathan M.; Zhao, Yuhai; Lukiw, Walter J. (Frontiers in Neurology, 2022)
Microbiome-derived Gram-negative bacterial lipopolysaccharide (LPS) has been shown by multiple laboratories to reside within AD-affected brain neocortical and hippocampal neurons. LPS and other pro-inflammatory stressors strongly induce a defined set of NF-kB (p50/p65)-sensitive human microRNAs including a brain-enriched Homo sapien microRNA-30b-5p (hsa-miRNA-30b-5p; miRNA-30b). Here we provide evidence that this neuropathology-associated miRNA, known to be up-regulated in Alzheimer’s disease (AD) brain and LPS-stressed human neuronal-glial (HNG) cells in primary culture targets the neurofilament light (NF-L) mRNA 3’-untranslated region (3’-UTR) conducive to the post-transcriptional down-regulation of NF-L expression observed within LPS-stressed HNG cells. A deficiency of NF-L is associated with a consequent atrophy of the neuronal cytoskeleton and disruption of synaptic organization. Interestingly miRNA-30b has previously been shown to be highly expressed in amyloid-beta (Aβ) peptide-treated animal and cell models and Aβ peptides promote LPS entry into neurons. Increased miRNA-30b expression induces neuronal injury, neuron loss, neuronal inflammation, an impairment of synaptic transmission and synaptic failure in neurodegenerative disease and transgenic murine models. This gut microbiota-derived LPS-NF-kB-miRNA-30b-NF-L pathological signaling network: (i) under-scores a positive pathological link between the LPS of gastrointestinal (GI)-tract microbes and the inflammatory neuropathology, disordered cytoskeleton and disrupted synaptic signaling of the AD brain and stressed brain cells; and (ii) is the first example of a microbiome-derived neurotoxic glycolipid having significant detrimental miRNA-30b-mediated actions on the expression of NF-L, an abundant neuron-specific filament protein known to be important in the maintenance of neuronal cell shape, axonal caliber and synaptic homeostasis.